Reconstructing Assessment in Islamic Religious Education: A Multicultural Framework for Diversity Awareness and Social Cohesion - Nurul Latifatul Inayati; Musa Asy'arie; Sekar Ayu Aryani; Muthoifin Muthoifin (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
Current assessment practices in Islamic Religious Education (IRE) remain largely dominated by cognitive and textual measures, limiting their capacity to evaluate students’ attitudes, behaviours, and social engagement in multicultural contexts. This study aims to analyse the limitations of conventional IRE assessment and reconstruct a multicultural-based evaluation framework that promotes diversity awareness and social cohesion. Using a Systematic Literature Review (SLR) guided by the PRISMA protocol, this study examined 51 Scopus-indexed articles published between 2020 and 2025. The findings reveal that conventional assessment models tend to be superficial because they emphasise conceptual understanding while neglecting affective, behavioural, and social dimensions. The review also shows that adaptive multicultural learning strategies, including contextual, dialogic, collaborative, and authentic approaches, are more effective in cultivating tolerance and inclusive attitudes. This study proposes a reconstructed CIPP-based assessment framework encompassing Context, Input, Process, and Product evaluation. The framework contributes to IRE evaluation theory by shifting assessment from academic measurement toward transformative evaluation of value internalisation, inclusive practice, and social harmony.